2018
DOI: 10.1515/opar-2018-0019
|View full text |Cite
|
Sign up to set email alerts
|

The Complexities of Metal Detecting Policy and Practice: A Response to Samuel Hardy, ‘Quantitative Analysis of Open-Source Data on Metal Detecting for Cultural Property’ (Cogent Social Sciences 3, 2017)

Abstract: In his paper ‘Quantitative analysis of open-source data on metal detecting for cultural property’, Samuel Hardy suggested that permissive policy is ineffective in minimizing the damage done to cultural heritage by non-professional metal detecting. This response paper contests the basic assumptions upon which this analysis is based. While Hardy‘s comparative, quantitative approach is laudable, it is founded in a biased and simplistic outlook on the metal detecting phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…In Denmark, for example, only a small minority of 485 finds (1.6 per cent) of the total amount of 30,224 finds recorded in the DIME scheme up to July 2019 were found in the context of possibly undisturbed landscapes. Likewise, of the 79,353 finds logged with the PAS in 2017, 93 per cent came from cultivated land; just over 2 per cent from grassland, and 2 per cent from the foreshore (Lewis, 2018). Normally, any contextual associations of an object in the soil have been compromised by the mixing effect of ploughing and other agricultural processes.…”
Section: Preservation Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Denmark, for example, only a small minority of 485 finds (1.6 per cent) of the total amount of 30,224 finds recorded in the DIME scheme up to July 2019 were found in the context of possibly undisturbed landscapes. Likewise, of the 79,353 finds logged with the PAS in 2017, 93 per cent came from cultivated land; just over 2 per cent from grassland, and 2 per cent from the foreshore (Lewis, 2018). Normally, any contextual associations of an object in the soil have been compromised by the mixing effect of ploughing and other agricultural processes.…”
Section: Preservation Issuesmentioning
confidence: 99%
“…We contend that the systematic recording and study of metal-detected objects under a cooperative scheme yields a greater gain in knowledge about the past than is possible under a restrictive scheme. By contrast, in most restrictive contexts, detector finds are largely unreported and information about them is, therefore, difficult to access and interpret (see for example Hardy, 2017; Deckers et al, 2018). The mistrust between professional archaeologists and hobby detectorists, often a consequence of restrictive legislation and disapproving attitudes, further obscures the availability of reliable metal-detected finds data.…”
Section: Explaining the Visionmentioning
confidence: 99%
“…The most recent estimation is provided by Hardy (2017), who suggests that around 96 percent of recordable objects are not reported. This figure has been challenged by Deckers et al 2018. 22 Daubney 2017, 792.…”
Section: Existing Knowledge Of the Problemmentioning
confidence: 99%
“…For example, it leads to the nonsensical conclusion that damage by licit detectorists is 81 times higher when 10% of their finds go unreported than when 90% of their finds are unreported. Possibly Deckers et al (2018) actually meant this term to be the proportion of reported finds. In other words, the two terms may have been accidentally reversed, but making that correction still does not make this expression yield what Hardy was measuring.…”
Section: Characterization Of Hardy's Measure Of Cultural Damagementioning
confidence: 99%
“…An article in Open Archaeology by Deckers et al (2018) critiques Hardy's (2017) analysis of the impact of the metal-detecting hobby on archaeological resources in a number of mostly anglophone countries. Both articles, following in the wake of several others (e.g., Campbell, 2013;Deckers et al, 2016;Dobat & Jensen, 2016;Thomas, 2013), raise substantive issues regarding metal detecting, and particularly the importance of evidence-based policy for the restriction, regulation or permission of metal detecting.…”
Section: Introductionmentioning
confidence: 99%